Second Heart Field-specific expression of Nkx2-5 requires promoter proximal interaction with Srf - Clark, Christopher D. (Mech Dev, 2020)
The cardiac homeobox transcription factor Nkx2-5 is a major determinant of cardiac identity and cardiac morphogenesis. Nkx2-5 operates as part of a complex and mutually reinforcing network of early transcription factors of the homeobox, GATA zinc finger and MADS domain families to initiate the program of cardiac development and differentiation, particularly in outflow tract precursor cells in the second heart field (SHF). We have now found evidence for another aspect of cardiac transcription factor cooperativity between Nkx2-5 and the cardiac enriched MADS domain transcription factor Srf. Specifically, Srf interaction with an evolutionarily conserved binding site in the Nkx2-5 CpG island-like proximal promoter is required for cardiac specific expression mediated by an SHF enhancer, and for combinatorial activation of these elements by cardiac transcription factors. These results provide further insight into cooperative gene regulation during cardiogenesis at the level of promoter-enhancer interactions.